Quantum leap. Season 3 [videorecording (DVD)]. - Bakula, Scott; Stockwell, Dean, 1936-2021; Pratt, Deborah (Deborah M.) (Mill Creek Entertainment, 2017)
Join Dr. Sam Beckett, a time traveler lost in time, who temporarily leaps into the bodies and lives of other people to "put right what once went wrong". Accompanied by Al, a wise-cracking holograph that only Sam can see and hear, Sam twists the hands of fate with each heart-pounding, action-packed adventure in the hopes that he can someday complete the mission that will take him home.